Potential impact of the 2017 ACC/AHA guideline on high blood pressure in normotensive patients with stable coronary artery disease: insights from the CLARIFY registry. (14th August 2018) - Vidal-Petiot, Emmanuelle; Sorbets, Emmanuel; Bhatt, Deepak L; Ducrocq, Gregory; Elbez, Yedid; Ferrari, Roberto; Ford, Ian; Tardif, Jean-Claude; Tendera, Michal; Fox, Kim M; Steg, Philippe Gabriel
Abstract: Aims: The 2017 American College of Cardiology/American Heart Association (ACC/AHA) guideline on high blood pressure (BP) lowered the threshold defining hypertension and BP target in high-risk patients to 130/80 mmHg. Patients with coronary artery disease and systolic BP 130–139 mmHg or diastolic BP 80–89 mmHg should now receive medication to achieve this target. We aimed to investigate the relationship between BP and cardiovascular events in 'real-life' patients with coronary artery disease considered as having normal BP until the recent guideline. Methods and results: Data from 5956 patients with stable coronary artery disease, no history of hypertension or heart failure, and average BP <140/90 mmHg, enrolled in the CLARIFY registry (November 2009 to June 2010), were analysed. In a multivariable-adjusted Cox proportional hazards model, after a median follow-up of 5.0 years, diastolic BP 80–89 mmHg, but not systolic BP 130–139 mmHg, was associated with increased risk of the primary endpoint, a composite of cardiovascular death, myocardial infarction, or stroke (hazard ratio 2.15, 95% confidence interval 1.22–3.81 vs. 70–79 mmHg and 1.12, 0.64–1.97 vs. 120–129 mmHg). No significant increase in risk for the primary endpoint was observed for systolic BP <120 mmHg or diastolic BP <70 mmHg. Conclusion: In patients with stable coronary artery disease defined as having normal BP according to the 140/90 mmHg threshold, diastolic BP 80–89 mmHg was associated with increased cardiovascular risk, whereas systolic BP 130–139 mmHg was not, supporting the lower diastolic but not the lower systolic BP hypertension-defining threshold and treatment target in coronary artery disease. ClinicalTrials identifier: ISRCTN43070564.